Do distracting activities increase tolerance for an infant cry?. Issue 1 (25th October 2016) - Glodowski, Kathryn; Thompson, Rachel
Abstract : Professionals recommend parents engage in distracting activities to mitigate negative effects of inconsolable infant crying (e.g., Deyo, Skybo, & Carroll, 2008; Goulet et al., 2009). We evaluated the availability of alternative activities on six undergraduates' tolerance for a recorded infant cry; three students tolerated the cry longer when distracting activities were available. Our results show that distracting activities could decrease the aversiveness of inconsolable infant crying for some individuals; additional research in natural caregiving situations will help determine the generality and social validity of this finding.